Targeting Molecular Pathways in Intracranial Metastatic Disease - Venur, Vyshak Alva; Cohen, Justine V.; Brastianos, Priscilla K. (Frontiers in Oncology, 2019)
The discovery and clinical application of agents targeting pivotal molecular pathways in malignancies such as lung, breast, renal cell carcinoma, and melanoma have led to impressive improvements in clinical outcomes. Mutations in epidermal growth factor receptor (EGFR), and rearrangements of anaplastic lymphoma kinase (ALK) are targetable in lung cancer, while BRAF mutations have been successfully targeted in metastatic melanoma. Targeting estrogen receptors, cyclin dependent kinases, and HER2 (Human Epidermal Receptor) have resulted in improvement in survival in breast cancer. Major strides have been made in the management of metastatic renal cell carcinoma by targeting the vascular endothelial growth factor (VEGF) pathway. However, intracranial metastases remain a major hurdle in the setting of targeted therapies. Traditional treatment options for brain metastases include surgery, whole brain radiation therapy (WBRT), and stereotactic radiosurgery (SRS). Surgery is effective in symptomatic patients with dominant lesions or solitary intracranial metastases, however, recovery time can be prolonged, often requiring an interruption in systemic treatment. WBRT and SRS provide symptomatic relief and local control but data on improving overall survival is limited. Most targeted therapies which provide extracranial control have limited penetration through the blood brain barrier. Given the limited therapeutic options and increasing prevalence of brain metastases, finding new strategies for the management of intracranial metastatic disease is critical. Genomic analysis of brain metastases has led to a better understanding of variations in the driver mutations compared to the primary malignancy. Furthermore, newer generations of targeted agents have shown promising intracranial activity. In this review, we will discuss the major molecular alterations in brain metastases from melanoma, lung, breast, and renal cell carcinoma. We will provide an in-depth review of the completed and ongoing clinical trials of drugs targeting the molecular pathways enriched in brain metastases.